Metacognitive Analysis of Students in Solving Mathematics Problem - Defi, Sri Adi; Haryono, Yulia; Jufri, Lucky Heriyanti (Al-Khawarizmi, 2022)
This research is motivated by the lack of students' understanding of their thinking skills and students cannot determine the right strategy to overcome the problems encountered in solving mathematical problems. The purpose of this study was to find out how the metacognitive level of students in solving math problem solving problems in class IX.1 students of SMPN 26 Padang. This type of research is descriptive quantitative. The subject of this research is class IX.1 SMP Negeri 26 Padang. The instruments used are tests and interviews. The test is used to determine the metacognitive level of students in solving problem solving problems. Interviews were used to find out more about the metacognitive level in terms of students' understanding. The results showed that as many as 35.71% of students were at the metacognitive level of Tacit Use, as many as 35.71% of students had the metacognitive level of Aware Use, and as many as 28.58% of students had the metacognitive level of Strategic use. Students who have a high group metacognitive ability score in the classroom are at the Strategic Use metacognitive level. Students who have a moderate group metacognitive ability score in the class are at the Aware Use metacognitive level. and students who have a low group metacognitive ability score in the class are at the metacognitive level of Tacit Use.